2004
DOI: 10.1590/s0102-311x2004000700014
|View full text |Cite
|
Sign up to set email alerts
|

Algumas repercussões emocionais negativas da gravidez precoce em adolescentes do Município do Rio de Janeiro (1999-2001)

Abstract: This study analyzed the association between early pregnancy and negative emotional repercussions for adolescents, according to socio-demographic and psychosocial variables. The study interviewed 1,228 adolescents in maternity hospitals in the City of Rio de Janeiro. Emotional repercussions were evaluated with negative self-assessment variables, showing little or no expectation towards the future, as well as psychological distress. The chi2 test and odds ratio were used to analyze the data. Adolescents who repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
24

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 11 publications
0
7
0
24
Order By: Relevance
“…4 Ainda, a gravidez nessa fase da vida pode levar a problemas sociais, como a evasão escolar, redução das oportunidades de qualificação profissional e consequente dificuldade no acesso ao mercado de trabalho, instabilidade conjugal e preconceito por parte da sociedade. 1,7,8 Diante da relevância do problema, a publicação de estudos sobre a saúde sexual e reprodutiva de jovens e adolescentes tem se intensificado nos últimos anos, os quais têm contribuído para a implementação de políticas públicas voltadas ao problema em todo o mundo.…”
Section: Introductionunclassified
“…4 Ainda, a gravidez nessa fase da vida pode levar a problemas sociais, como a evasão escolar, redução das oportunidades de qualificação profissional e consequente dificuldade no acesso ao mercado de trabalho, instabilidade conjugal e preconceito por parte da sociedade. 1,7,8 Diante da relevância do problema, a publicação de estudos sobre a saúde sexual e reprodutiva de jovens e adolescentes tem se intensificado nos últimos anos, os quais têm contribuído para a implementação de políticas públicas voltadas ao problema em todo o mundo.…”
Section: Introductionunclassified
“…Often, teenage mothers do not return to school. 15 A cross-sectional study carried out in Rio de Janeiro 18 showed that teenagers who mentioned a negative reaction on the part of their family felt less valued, with very few expectations concerning the future and showed greater psychological suffering when compared to those who found support in their family. Besides that, teenagers who did not attend school before becoming pregnant also presented low self-esteem and little expectation concerning their future, when compared to teenagers who left school during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, teenagers who did not attend school before becoming pregnant also presented low self-esteem and little expectation concerning their future, when compared to teenagers who left school during pregnancy. 18 Making inadequate use of prenatal care is also one of the characteristics of teenage pregnancy 1,5 that negatively infl uences the biological outcomes of the pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…A literatura sobre essa temática é ampla, sendo que a maior parte dos estudos tem delineamento transversal e quantitativo, enfatizando aspectos negativos da vivência, enquanto os estudos qualitativos tendem a revelar aspectos positivos e adaptativos em relação à maternidade. Dentre alguns dos problemas comumente relacionados à esta condição, destacam-se os riscos para a saúde de mãe e filho, o baixo nível socioeconômico, o início precoce da menarca e relações sexuais, abandono escolar, violência sexual entre mulheres com menos de 14 anos, sofrimento psíquico e dificuldades na adoção de comportamentos contraceptivos, que se constituem como experiências subjetivas e graduais, adquiridas ao longo do tempo (Brandão & Heilborn, 2006;Caputo & Bordin, 2007;Cavasin et al, 2004;Cerqueira-Santos, Paludo, Schirò, & Koller, 2010;Levandowski, Piccinini, & Lopes, 2008;Sabroza, Leal, Souza, & Gama, 2004;Taquette, 2008).…”
unclassified